Abu Dhabi International Petroleum Exhibition and Conference 2002
DOI: 10.2118/78562-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Poroelastic Analysis to Address the Impact of Depletion Rate on Wellbore Stability in Openhole Horizontal Completions

Abstract: This paper highlights the development of a coupled poroelastic geomechanical and fluid flow model which incorporates field and lab data with the objective to constrain the full in-situ stress tensor and rock strength in order to predict the stability of open hole horizontal completions during reservoir depletion. Results of a four-year comprehensive testing and monitoring program conducted to assess the extent of hole instability during shut-in and flowing periods1 indicated that there was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The effects of PSC on stress magnitudes and tectonic stress regimes should be taken into account in planning additional wells for secondary or tertiary production measures. Furthermore, the PSC methodology should be considered for the early times of injection when (Teufel et al, 1991), Groningen (Hettema et al, 1998), Shaybah (Salamy and Finkbeiner, 2002), Gunung Kembang (Dwi Hudya et al, 2007), Eugene Island Block 330 (Finkbeiner and Zoback, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of PSC on stress magnitudes and tectonic stress regimes should be taken into account in planning additional wells for secondary or tertiary production measures. Furthermore, the PSC methodology should be considered for the early times of injection when (Teufel et al, 1991), Groningen (Hettema et al, 1998), Shaybah (Salamy and Finkbeiner, 2002), Gunung Kembang (Dwi Hudya et al, 2007), Eugene Island Block 330 (Finkbeiner and Zoback, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Tests also indicated that there was a general decrease in strength with increased porosity and that most of the core samples were behaving in a ductile manner. Salamy and Finkbeiner (2002) remarked that the reason all the horizontal wells remained open was because of the "yield zone" behavior of borehole instability, which keeps the rock in the immediate vicinity of the borehole in a failed but semistable state. This instability has the potential to cause borehole restriction, elongation, fill, washout, and, eventually, borehole collapse .…”
Section: Mechanical Properties Of Shu'aiba Rocksmentioning
confidence: 99%
“…Extensive petrophysical analysis has been conducted on Shaybah rock samples (e.g., Okasha et al 2000;Okasha and Funk 2002;Okasha et al 2003;Okasha et al 2005;Okasha et al 2006;Hughes et al 2004;Salamy et al 1999;Salamy and Finkbeiner 2002). These include conventional measurements (porosity, permeability, grain density, and CT-scan-based bulk density/porosity), special-core-analysis measurements [relative permeability, wettability, mercury capillary pressure, electrical properties, and nuclear magnetic resonance (NMR)], and geologic core descriptions [XRD, XRF, fluorescence, thin-section petrography, scanning electron microscopy (SEM), and visual core descriptions].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations